Synthesis of glycerol carbonate from transesterification of glycerol with dimethyl carbonate catalyzed by CaO from natural sources as green and economical catalyst. (2018) - Roschat, Wuttichai; Phewphong, Sunti; Kaewpuang, Teadkait; Promarak, Vinich
Abstract: CaO catalysts derived from natural sources were investigated in the transesterification of dimethyl carbonate with glycerol to produce glycerol carbonate. The obtained CaO catalysts were characterized by several techniques, namely TG-DTA, XRD, XRF, BET surface area, SEM, FT-IR, CO2 -TPD, and Hammett indicator test. The transesterification was simply monitored and analyzed by NMR technique. Under the optimized reaction conditions of dimethyl carbonate to glycerol molar ratio of 3:1, catalyst loading amount of 3 wt.% and reaction temperature of 80 °C; over 92.1% yield of glycerol carbonate product could be achieved within 2 h.